2009
DOI: 10.1007/s11172-010-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of substituted dibenz[b,f]oxepines from 2,4,6-trinitrotoluene

Abstract: 1,3 Dinitro[b,f]dibenzoxepine undergoes nucleophilic substitution with O and S nucleo philes, the nitro group at position 1 (peri nitro group) being selectively replaced. The factors responsible for the selectivity of the reaction are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Bu sebeple mevcut ürünlerin performansını iyileştirmek ve zorlu gereksinimlerini karşılamak için son zamanlarda pek çok çalışma yapılmış birçok yeni enerjik malzemeler ortaya çıkmıştır [14][15][16][17]. Hidrojen, oksijen, azot ve karbon yoğunluklu en çok kullanılan enerjik malzemeler arasında, TNT [18][19][20][21], 1,3,5,7-tetranitro-1,3,5,7-tetrazosin (HMX) [22][23][24][25], 1,3,5-trinitro-1,3,5-triazin (RDX), [26,27], triaminotrinitrobenzen (TATB) [28][29][30][31][32], 2,4, 6,8,10,12 hekzanitro-2,4,6,8,10,12-hekzaazaisowurtzitan (CL-20) [33,34], oktanitroküban, [35] ve 4,10dinitro-4,10-diaza-2,6,8,12-tetraoksaizowurtzitan (TEX) [36,37] gibi maddeler bulunmaktadır. Ancak, bu nitro içeriği yüksek patlayıcıların çoğu son derece çevre kirletici özelliktedir.…”
Section: Introductionunclassified
“…Bu sebeple mevcut ürünlerin performansını iyileştirmek ve zorlu gereksinimlerini karşılamak için son zamanlarda pek çok çalışma yapılmış birçok yeni enerjik malzemeler ortaya çıkmıştır [14][15][16][17]. Hidrojen, oksijen, azot ve karbon yoğunluklu en çok kullanılan enerjik malzemeler arasında, TNT [18][19][20][21], 1,3,5,7-tetranitro-1,3,5,7-tetrazosin (HMX) [22][23][24][25], 1,3,5-trinitro-1,3,5-triazin (RDX), [26,27], triaminotrinitrobenzen (TATB) [28][29][30][31][32], 2,4, 6,8,10,12 hekzanitro-2,4,6,8,10,12-hekzaazaisowurtzitan (CL-20) [33,34], oktanitroküban, [35] ve 4,10dinitro-4,10-diaza-2,6,8,12-tetraoksaizowurtzitan (TEX) [36,37] gibi maddeler bulunmaktadır. Ancak, bu nitro içeriği yüksek patlayıcıların çoğu son derece çevre kirletici özelliktedir.…”
Section: Introductionunclassified
“…Traditional energetic materials, such as cyclo-1,3,5-trimethylene-2,4,6-trinitamine (RDX), , 2,4,6-trinitrotoluene (TNT), and 1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX), have been used for a variety of military purposes and civilian applications. Many catastrophic explosions of these compounds urge researchers to synthesize new energetic materials with higher safety as well as good performance. As the desirable requirements, the modern explosives and propellants should possess good thermal stability, impact and shock insensitivity, and other better performance …”
Section: Introdutionmentioning
confidence: 99%
“…[6d, 7, 10, 13] Furthermore, the nucleophilic aromatic substitution reaction (S N Ar) has been widely used for the formation of biaryl ethers. [8,14,15] Ring expansion by Wagner-Meerwein rearrangement, [16] Mn 2 + -based oxidative radical rearrangement, [17] sequential Heck reaction and Pd-catalyzed etheration, [18] as well as metal-free synthesis [19] are some more strategies reported for the synthesis of dibenzoA C H T U N G T R E N N U N G [b,f]oxepins. As part of our research program towards the synthesis of natural products utilizing ring-closing metathesis (RCM) [19] and to develop a general synthetic protocol for the synthesis of bauhiniastatins, we found that RCMs [20] for the synthesis of fully unsaturated or aromatic compounds are relatively limited.…”
Section: Introductionmentioning
confidence: 99%